2013
DOI: 10.5455/gmj-30-2012-115
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum discharge readiness situation of women who had vaginal deliveries

Abstract: ÖzetBu araştırma vajinal doğum yapmış, postpartum dönemde olan kadınların hastaneden taburculuğa hazır oluşluklarının değerlendirilmesi amacıyla tanımlayıcı ve kesitsel tipte planlanmıştır. Araştırma, 01.03.2012-01.04.2012 tarihleri arasında bir devlet hastanesinde vajinal doğum yapmış 110 kadına uygulanmıştır. Veri toplama aracı olarak birey tanılama formu ve Hastane Taburculuğuna Hazır Oluşluk Ölçeği-Yeni Doğum Yapmış Anne Formu (HTHÖ-YDAF) kullanılmıştır. Katılımcıların yaş ortalaması 25.30± 5.32 olup %38.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
2
17
1
Order By: Relevance
“…Studies investigating readiness for hospital discharge indicate that readiness of mothers who received training was significantly higher, which is a parallel finding with our study (Weiss and Lokken 2009;Dağ et al. 2013;Altuntuğ et al.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Studies investigating readiness for hospital discharge indicate that readiness of mothers who received training was significantly higher, which is a parallel finding with our study (Weiss and Lokken 2009;Dağ et al. 2013;Altuntuğ et al.…”
Section: Discussionsupporting
confidence: 82%
“…Weiss et al (2004) found that number of deliveries is one of the factors that affects readiness for hospital discharge. Dağ et al (2013) found that multiparous mothers had higher readiness for hospital discharge. Mothers' being primiparous is reported to have negative effects on readiness for hospital discharge.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Early or late discharge is a conflicting issue both in our country and in the world. Early discharge in the postpartum period has evolved due to the restriction of health insurances which offered shorter hospital stays for postpartum women with no major physical or medical problem (Da g, D€ onmez, S ßen, & S ßirin, 2013). Early discharge for obstetric patients has been recommended in the USA since 1940s.…”
mentioning
confidence: 99%